The Effectiveness of Problem Based Learning and Project Based Learning Model to Improve Natural Science Study Outcomes - Hanipah, Sri; Florentinus, Totok Sumaryanto; Rifai RC, Achmad (Universitas Negeri Semarang, 2018)
The limited creativity of teachers in choosing the right learning model has an impact on the students' learning outcomes. This study aims to compare the effectiveness of problem-based learning and project-based learning model in improving the outcomes of science learning. The type of research is experimental research with pretest-posttest design. The population is the students in the seventh grade of SMP Bina Insani Semarang. The samples were taken by cluster random sampling technique. Research data were analyzed by using independent test sample t test at α 0.05. The results showed: (1) there were differences of cognitive learning outcomes between group based learning and project based learning with significance value 0.001 < 0.05, (2) there was no significant difference between problem based learning and project based learning groups in improving students’ caring attitude toward environment with a significance value of 0.666 > 0.05. So, the conclusion is problem based learning models is more effective to improve students' cognitive learning outcomes than project based learning models. Both models do not show significant differences in improving students' environmental care attitudes. The benefits of this research can find a synthesis to add khasanah in the field of science learning.